Bio-affinity ultra-filtration combined with HPLC-ESI-qTOF-MS/MS for screening potential α-glucosidase inhibitors from Cerasus humilis (Bge.) Sok. leaf-tea and in silico analysis. (30th March 2022) - Li, Songjie; Wang, Ruimin; Hu, Xiaoping; Li, Congfa; Wang, Lu
Graphical abstract: Highlights: Cerasus humilis leaf-tea (CLT) was a good source rich in α -glucosidase inhibitors ( α -GIs) Phenolic compositions of the CLT extracts were identified for the first time. Ultra-filtration plus LC-MS/MS technique was used to screen the α -GIs rapidly. Myricetin, avicularin, quercitrin, prunin and guajavarin were major α -GIs in CLT. Interactions mechanisms of the screened α -GIs on α -glucosidase were clarified. Abstract: Cerasus humilis (Bge.) Sok. leaf-tea (CLT) has a potential anti- α -glucosidase effect. However, its anti- α -glucosidase functional compositions remain unclear. Results showed that 70% methanol extract of CLT (IC50 = 36.57 μg/mL) with the highest total phenolic/flavonoid contents exhibited significantly higher α -glucosidase inhibitory activity ( α -GIA) than acarbose (IC50 = 189.57 μg/mL). Additionally, phenolic constituents of the CLT extract were analyzed for the first time in this work. Ten major potential α -glucosidase inhibitors ( α -GIs) with high bio-affinity degree in the CLT extract were recognized using a bio-affinity ultra-filtration and HPLC-ESI-qTOF-MS/MS method. In vitro α -GIA assay confirmed that myricetin (IC50 = 36.17 μg/mL), avicularin (IC50 = 69.84 μg/mL), quercitrin, isoquercitrin, prunin and guajavarin were responsible for the α -GIA of the CLT extract. More importantly, the interaction mechanism between α -GIs and α -glucosidase was investigated via in silico analysis. This study provides a high-throughput screening platform for identification of the potential α -GIs from natural products.